Three-phase transformer arcing horns; neglected deadly components to birds (Avocetta, 2020)
Unprotected power transformers are known to create electrocution problems for wildlife. However, the role of three-phase transformer arcing horns and bird electrocutions has not been investigated. Arcing horns are rigid conductors sometimes deployed to protect insulators by providing a gap for lightning to jump across without damaging the equipment. To identify how birds are electrocuted by arcing horns we submitted a survey to 32 Iranian utility companies and examined 562 opportunistic utility outage records of bird electrocutions between 2018 to 2019. We documented 59 electrocuted birds and classified five types of arcing horn electrocutions based on where the carcasses were discovered. To mitigate such problems utilities sometimes remove arcing horns but doing so can be problematic to the power network. Using insulation is not entirely effective because the point of the upper rod can produce an electrical discharge to the head of a bird perching on the lower grounded rod. We provide alternative solutions.
Keywords: Acridotheres tristis; biological invasions; distribution; invasive alien species; impacts